Chemical characteristics of rainwater in central India - Patel, K.S.; Ambade, B.; Nicolás, J.; Yubero, E. (Інститут проблем природокористування та екології НАН України, 2009)
In the present work, the rainwater chemistry in the most industrialized area of central
India, Raipur city (capital, Chhattisgarh state) is described. The volume weighted
mean value (n=31) of pH, conductivity and TDS of the rainwater during monsoon season,
May – October, 2008 was 6.42, 483 μS and 237 mg l-1, respectively. The volume
weighted mean content of ions i.e. Cl-, NO3
-, SO4
2-, NH4
+, Na+, K+, Mg2+ and Ca2+ was
2.83, 2.71, 7.64, 0.73, 1.00, 0.92, 1.1 and 2.53 mg l-1, respectively. The variations, scavenging
and enrichment, correlations and sources of the ions in the rainwater are discussed. В данной работе описаны химические особенности дождевой воды в наиболее
индустриальной местности центральной Индии, город Райпур (столица штата
Шаттигарф). Показатели измерений (n=31) pH, проводности (ионы) и TDS в дождевой воде во время сезона муссона, май – октябрь, 2008 года были 6.42, 483 μS и
237 mg l-1 соответственно. Состав ионов представлен Cl-, NO3
-, SO4
2-, NH4
+, Na+, K+,
Mg2+ та Ca2+ с показателями 2.83, 2.71, 7.64, 0.73, 1.00, 0.92, 1.1 и 2.53 mg l-1. Также
обсуждаются вопросы вариативности показателей, их ошибки, связи и источники
ионов в дождевой воде. В даній роботі описані хімічні особливості дощової води в найбільш індустріальній місцевості центральної Індії, місто Райпур (столиця штату Шаттігарф). Показники вимірювань (n=31) pH, провідності (іони) та TDS у дощовій воді під час
сезону мусону, травень – жовтень, 2008 року були 6.42, 483 μS та 237 mg l-1 відповідно. Склад іонів представлений Cl-, NO3
-, SO4
2-, NH4
+, Na+, K+, Mg2+ та Ca2+ з показниками 2.83, 2.71, 7.64, 0.73, 1.00, 0.92, 1.1 та 2.53 mg l-1. Також обговорюються питання варіативності значень, їх похибок, зв’язків та джерел іонів у дощовій воді.